Flue gas dust removal and denitration process

Through multi-step synergistic process and material innovation, wet washing, corrugated plate catalysts and modified adsorbents are used to solve the problems of low dust removal and denitrification efficiency and easy catalyst deactivation in traditional flue gas purification technology, achieving efficient, stable and economical integrated removal of dust and NOx.

CN120479186APending Publication Date: 2025-08-15JIANGSU NINGTIAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510913079.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

In traditional flue gas purification technology, dust removal and denitrification efficiency is low, catalysts are prone to deactivation, high operating costs, and the existing processes are complex and expensive, making it difficult to achieve integrated deep removal of dust and NOx.

Method used

A multi-step synergistic process is adopted, including wet washing in the pretreatment area, corrugated plate catalyst in the catalytic reaction area and adsorbent in the deep purification area. Through process integration and material innovation, alkaline solution spraying with pH 8-10, supported metal oxide catalyst, nano-silica protective layer and modified adsorbent are used to optimize the catalyst structure and material combination to achieve efficient coordinated removal of dust and NOx.

Benefits of technology

It achieves efficient, stable and economical integrated removal of dust and NOx, reduces energy consumption, expands the application scope of process, improves purification efficiency and reduces operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a flue gas dust removal and denitration process, and belongs to the technical field of flue gas treatment.The denitration process comprises the following steps that flue gas to be treated is introduced into a pretreatment zone, large-particle dust and part of acid gas in the flue gas are removed, the treated flue gas is introduced into a catalytic reaction zone, and under the action of a corrugated plate catalyst, the flue gas is subjected to denitration treatment; spraying a reducing agent into the flue gas; introducing the flue gas subjected to the catalytic reaction into a deep purification area, and adsorbing and purifying residual fine dust by adopting an adsorbent; and then the treated flue gas reaching the standard is discharged. Through process integration and material innovation, the problems of low dust removal and denitration efficiency, easy catalyst deactivation, high operation cost and the like in the traditional technology are solved, and the method has the advantages of high purification efficiency, low energy consumption, wide application range and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flue gas treatment, and in particular relates to a flue gas dust removal and denitrification process. Background Art

[0002] To meet increasingly stringent environmental regulations (such as ultra-low emission standards), flue gas purification technology has become a research hotspot. Traditional processes typically utilize a separate treatment model combining electrostatic precipitation (ESP) and selective catalytic reduction (SCR), but these processes have significant limitations. ESP is inefficient for removing fine dust (especially particles below PM2.5), while SCR technology requires high temperatures (300-400°C), resulting in high energy consumption and catalyst susceptibility to dust clogging or sulfur poisoning. Furthermore, while existing wet scrubbing technologies can synergistically remove sulfur and dust, the alkaline absorbent easily reacts with CO2 in the flue gas, leading to scaling and reagent waste, and their effectiveness in removing NOx is limited. In recent years, researchers have attempted to improve performance by improving catalysts or optimizing adsorption materials, but improvements in a single material or process have proven difficult to overcome technical bottlenecks. For example, conventional honeycomb catalysts have a low specific surface area and insufficient reactive sites; conventional activated carbon has a limited NOx adsorption capacity and is difficult to regenerate. While some integrated processes can reduce energy consumption, they are complex and require high investment costs.

[0003] Therefore, there is an urgent need to develop an efficient, stable and economical multi-pollutant coordinated control technology to achieve integrated deep removal of dust and NOx.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The first purpose of the present invention is to provide a flue gas dust removal and denitrification process, which solves the problems of low dust removal and denitrification efficiency, easy deactivation of catalysts, and high operating costs in traditional technologies through process integration and material innovation. It has the advantages of high purification efficiency, low energy consumption and a wide range of applications.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0007] A flue gas dust removal and denitrification process comprises the following steps:

[0008] The flue gas to be treated is passed into the pretreatment area, and a wet scrubbing method is used to remove large dust particles and some acidic gases in the flue gas. The wet scrubbing method adopts a multi-stage spraying system. The spraying liquid is an alkaline solution with a pH value of 8-10, and the volume ratio of the spraying liquid to the flue gas is 1:50-1:100;

[0009] The treated flue gas is introduced into the catalytic reaction zone, and the reducing agent is sprayed into the flue gas under the action of the corrugated plate catalyst;

[0010] The flue gas after the catalytic reaction is then passed into the deep purification zone, where adsorbent is used to adsorb and purify the remaining fine dust;

[0011] The treated flue gas that meets the standards will then be discharged.

[0012] The flue gas dust removal and denitrification process provided by the present invention realizes the efficient integrated removal of dust and nitrogen oxides in the flue gas through the synergistic effect of multiple steps. First, a wet scrubbing method is used in the pretreatment area, and a multi-stage spray system is adopted. The spray liquid is an alkaline solution with a pH value of 8-10, and its volume ratio to the flue gas is controlled between 1:50 and 1:100, thereby effectively neutralizing the acidic gas in the flue gas through the alkaline solution. At the same time, large particles of dust are removed through the physical effect of multi-stage spraying. The low ratio design of the spray liquid to the flue gas not only ensures the scrubbing effect, but also avoids scaling or secondary pollution caused by excessive use of reagents. In addition, the alkaline solution is a mixed solution of sodium hydroxide and sodium carbonate. The synergistic effect of the two can balance the reaction activity and cost. The buffering effect of sodium carbonate can also reduce pH fluctuations and enhance system stability. In the wet scrubbing stage, a composite auxiliary agent (sodium polyacrylate and sodium dodecylbenzene sulfonate) is added. Its function is to improve the wettability and dispersibility of the spray liquid, thereby improving the dust capture efficiency. The design of the pretreatment zone not only creates a cleaner flue gas environment for subsequent catalytic reactions, but also reduces the risk of catalyst sulfur poisoning through preliminary deacidification. After the flue gas enters the catalytic reaction zone, it reacts with the injected reducing agent under the action of the corrugated plate catalyst.

[0013] Preferably, as a further specific embodiment, the corrugated plate catalyst is a supported metal oxide catalyst, and the active ingredients are a mixture of vanadium, tungsten and titanium; the corrugated plate structure of the corrugated plate catalyst is arranged in a sinusoidal or trapezoidal wave pattern, with a wave height of 5-20 mm and a wave spacing of 10-50 mm; the carrier of the corrugated plate catalyst is porous cordierite ceramic.

[0014] The present invention also further defines the corrugated plate catalyst and describes in detail its active ingredients, structural characteristics and carrier materials. From the perspective of the selection of active ingredients, the combination of vanadium, tungsten and titanium is not a random combination, but is based on their respective catalytic properties and synergistic effects. Vanadium is the most commonly used active component in selective catalytic reduction technology and is widely recognized for its high activity and selectivity in NOx reduction reactions, especially its excellent performance in the medium and high temperature ranges. The addition of tungsten can increase the acidity of the catalyst and enhance its adsorption capacity for ammonia, while also inhibiting the sintering of vanadium oxide and improving the thermal stability of the catalyst. Titanium not only has a good specific surface area and pore structure as a carrier material, but also has certain catalytic activity itself, especially under low temperature conditions, it can synergize with other active components.

[0015] The present invention also specifies that the corrugated plates of the corrugated plate catalyst have a sinusoidal or trapezoidal arrangement, with a wave height of 5-20 mm and a wave pitch of 10-50 mm. This sinusoidal or trapezoidal wave design effectively increases the turbulence of the airflow, disrupting the laminar boundary layer, thereby enhancing the contact efficiency between the flue gas and the catalyst surface and increasing the reaction rate. This corrugated structure also reduces the pressure drop during airflow, lowering system energy consumption, which is particularly important for industrial applications treating large flue gas flows. Setting the wave height and wave pitch requires striking a balance between increasing contact area and controlling pressure drop: too low a wave height results in insufficient contact area, affecting reaction efficiency; too high a wave height may increase airflow resistance and increase energy consumption. Setting the wave pitch also requires balancing airflow distribution and catalyst utilization. By limiting the wave height to 5-20 mm and the wave pitch to 10-50 mm, the catalyst maintains sufficient reaction area while keeping the pressure drop within a reasonable range, achieving both high efficiency and low energy consumption.

[0016] The choice of carrier material is also crucial for the present invention. The carrier of the corrugated plate catalyst is porous cordierite ceramic. Cordierite is a ceramic material with a low thermal expansion coefficient that can withstand the thermal stress caused by flue gas temperature changes, preventing catalyst cracking or pulverization due to thermal shock. Its porous structure provides a high specific surface area, providing ample space for the loading and reaction of active components. In addition, cordierite has good mechanical strength, which can withstand the erosion of dust in the flue gas and extend the service life of the catalyst. These properties of porous cordierite ceramic make it an ideal carrier for corrugated plate catalysts, especially in flue gas environments with high dust content, where its durability is particularly important.

[0017] The corrugated plate catalyst of this invention, through its unique wave design, combines a high specific surface area with excellent anti-clogging properties, making it particularly suitable for treating flue gases with high dust content. Furthermore, the optimized combination of active components maintains high activity over a wide temperature range, reducing efficiency drops caused by flue gas temperature fluctuations. The mechanical and thermal stability of the carrier material ensures long-term, reliable operation of the catalyst in harsh industrial environments, reducing replacement frequency and maintenance costs.

[0018] Preferably, as a further specific embodiment, the surface of the corrugated plate catalyst is coated with a nano-silicon dioxide protective layer, and the thickness of the nano-silicon dioxide protective layer is 0.1-0.5 μm.

[0019] The present invention also provides multiple functional protections for the catalyst by coating a nano-silica protective layer on the surface of the corrugated plate catalyst, and the thickness of the protective layer is controlled within the range of 0.1-0.5 μm, thereby significantly improving its durability and catalytic efficiency in complex flue gas environments. The introduction of the nano-silica protective layer is not a simple surface modification, but is intended to solve the problem of easy deactivation of the catalyst. In the actual working conditions of flue gas treatment, the main challenges faced by the catalyst include agglomeration of active components caused by high-temperature sintering, chemical poisoning caused by acidic gases, and physical coverage of active sites by dust particles. These factors will cause the catalyst activity to gradually decrease, and the nano-silica protective layer effectively responds to these challenges through its unique physical and chemical properties. The design of its nano-scale thickness not only ensures sufficient protection performance, but also avoids the obstruction of the diffusion of reactants by too thick a coating. If it is too thin, the protection effect is insufficient, and if it is too thick, it will affect the mass transfer efficiency of the reactants.

[0020] In addition, nano-silica has extremely high thermal stability and chemical inertness, and can maintain structural stability in high-temperature flue gas environments, effectively blocking the direct effects of high temperatures on the active components of the catalyst, preventing the sintering and volatilization of active components such as vanadium and tungsten, thereby maintaining the long-term activity of the catalyst. At the same time, the silanol groups on the silica surface provide weakly acidic sites that are conducive to the adsorption and activation of ammonia, indirectly promoting the SCR reaction. The porous structure of the protective layer allows the reactant gas to diffuse freely to the active sites of the catalyst while blocking larger dust particles and droplets. This molecular sieve effect significantly reduces the risk of physical blockage. The protective layer's thickness range of 0.1-0.5μm matches the size of fine particulate matter commonly found in flue gas, effectively intercepting fine particles below PM2.5.

[0021] Preferably, as a further specific embodiment, the nano-silica protective layer is doped with 1-3% cerium oxide; the cerium oxide wraps platinum nanoparticles in a core-shell structure, and the content of the platinum nanoparticles is 0.05-0.1 wt% of the mass of the cerium oxide.

[0022] The present invention also deepens the technical innovation of nano-silica protective layer. By doping 1-3% of cerium oxide in the protective layer and wrapping platinum nanoparticles with a core-shell structure, a multi-level synergistic composite catalytic protection system is constructed. This technical feature optimizes the performance of the catalyst at the molecular level and achieves a dual improvement in protection function and catalytic activity. 3+ / Ce 4+The reversible conversion enables the prepared catalyst to dynamically adjust the local microenvironment according to changes in the oxygen content in the flue gas. When the oxygen content in the flue gas is insufficient, cerium oxide releases stored oxygen atoms to participate in the reaction, and can re-store oxygen atoms under oxygen-rich conditions. This intelligent adjustment mechanism significantly improves the catalyst's adaptability to operating condition fluctuations and is particularly suitable for dealing with unstable flue gas composition scenarios in actual industries such as coal-fired power plants.

[0023] In addition, the cerium oxide in the present invention is a core-shell structure that encapsulates platinum nanoparticles, thereby constructing a highly efficient catalytic micro-unit at the nanoscale. The platinum nanoparticles serve as low-temperature catalytic active centers, and after being encapsulated by the cerium oxide shell, they have many advantages. The cerium oxide shell prevents the agglomeration and sintering of the platinum nanoparticles at high temperatures, solving the common stability problem of precious metal catalysts. In addition, a strong metal-support interaction is generated between the cerium oxide and the platinum. This interaction changes the electronic state of the platinum and enhances its adsorption and activation ability for NOx and NH3. At the same time, the oxygen vacancies in the cerium oxide can promote the formation and conversion of reaction intermediates. In addition, the platinum content is strictly controlled within the trace range of 0.05-0.1wt%, which not only exerts the high catalytic activity of the precious metal but also controls material costs. Therefore, for the present invention, this core-shell structure design can also enable the reactant molecules to be preactivated when passing through the cerium oxide shell, and then undergo efficient conversion on the platinum core surface, greatly improving the reaction rate under low-temperature conditions. The catalyst can still maintain good activity in the low-temperature range of 150-200°C, breaking through the limitation of insufficient low-temperature activity of traditional vanadium-based catalysts.

[0024] In terms of anti-poisoning performance, the introduction of the cerium oxide-platinum nanocomposite structure significantly enhances the catalyst's resistance to sulfides and heavy metals. Cerium oxide has a preferential adsorption and oxidation effect on SO2, converting SO2 into sulfate and fixing it on the surface, preventing it from further poisoning the internal vanadium, tungsten and titanium active components. At the same time, the presence of platinum nanoparticles promotes the decomposition of sulfate, avoiding the deactivation problem of traditional catalysts caused by ammonium sulfate deposition. In addition, for heavy metals such as arsenic and lead that may be present in flue gas, the strong coordination ability of cerium oxide can capture these poisons and protect the core catalytic active sites. This dual protection mechanism enables the catalyst to perform well in treating flue gas generated by the incineration of high-sulfur coal or heavy metal-containing waste, greatly expanding the scope of application of the process.

[0025] The vanadium-tungsten-titanium main catalyst is responsible for conventional denitrification reactions in the medium- and high-temperature ranges, while the cerium oxide-platinum nanostructures focus on reaction activation in the low-temperature range. The two complement each other through the nanopores of the protective layer. When the flue gas temperature is low, the platinum-cerium oxide system takes the lead; as the temperature rises, the main catalyst gradually activates, forming a smooth transition to activity. Furthermore, the addition of cerium oxide improves the mechanical strength and thermal shock stability of the silica protective layer, enabling it to withstand the thermal stress caused by sudden changes in flue gas temperature. The uniform distribution of platinum nanoparticles prevents material degradation caused by the formation of local hot spots, and the core-shell structure prevents the migration and loss of active components.

[0026] Preferably, as a further specific embodiment, the specific surface area of the corrugated plate catalyst is 50-200m 2 / g, and a porosity of 40-70%; a carbon nanotube network is embedded in the corrugated plate catalyst, and the surface of the carbon nanotube is modified with amino functional groups.

[0027] In addition, the present invention further defines the structural characteristics of the corrugated plate catalyst by controlling the specific surface area to 50-200m 2 / g, the porosity is set to 40-70%, and a carbon nanotube network is embedded in the catalyst and the surface is modified with amino functional groups, thereby constructing a high-efficiency catalytic system with a multi-level pore structure and chemically active sites, fundamentally improving the mass transfer efficiency and reaction activity of the catalyst. Among them, the specific surface area is a key indicator for measuring catalyst activity. A too low specific surface area will lead to insufficient active sites and affect the reaction efficiency, while an excessively high specific surface area may sacrifice the structural stability of the material and increase the preparation cost. This optimized range not only ensures sufficient active site exposure, but also maintains the mechanical strength and service life of the catalyst. In addition, the precise control of porosity solves the contradiction between mass transfer limitation and activity maintenance in traditional catalysts. The appropriate pore structure can provide a rapid diffusion channel for the reactant molecules and provide sufficient interface area for the reaction. This dual-continuous phase porous structure allows NOx and NH3 in the flue gas to efficiently contact the active sites, and the reaction products can be separated in time to avoid blockage.

[0028] Furthermore, the embedded carbon nanotube network offers multiple performance enhancements to the catalyst. Physically, the carbon nanotubes, with their extremely high aspect ratio, form interconnected transport channels within the catalyst, significantly improving the diffusion kinetics of reactants and products. This open structure, particularly when treating flue gases with high dust content, effectively prevents pore blockage caused by particulate accumulation. From an electron conduction perspective, the excellent electrical conductivity of the carbon nanotubes facilitates rapid electron transport across the catalyst surface, which is particularly important for NOx reduction reactions involving multiple electron transfers. This enhanced electron conduction accelerates the conversion of reaction intermediates and improves the overall reaction rate. More importantly, the surface-modified amino groups introduce additional chemical adsorption sites. These amino groups specifically adsorb NOx molecules, enriching low-concentration NOx in the flue gas and increasing local reactant concentrations, thereby overcoming the kinetic limitations of conventional SCR reactions caused by insufficient NOx partial pressure. The macropores of the carbon nanotube network ensure rapid reactant transport, the mesopores provide the primary reaction sites, and the micropores provide additional active sites. This multi-level pore structure optimizes mass transfer from the macroscale to the nanoscale. The introduction of amino functional groups changes the electron distribution on the catalyst surface, forming electronic interactions with the vanadium, tungsten and titanium active components, regulating the redox properties of the metal oxide, making it more conducive to the selective reduction of NOx. Under the complex and variable conditions of actual flue gas composition, the hydrophobic properties of carbon nanotubes can also reduce the adsorption of water vapor on the catalyst surface, avoiding the problem of water molecules competing with reactants for active sites. This property is particularly important for treating high-humidity flue gas. From the perspective of anti-poisoning and durability, the rigid skeleton formed by the carbon nanotube network enhances the mechanical strength of the catalyst, capable of resisting the erosion and wear of particulate matter in the flue gas. The amino functional groups have a preferential adsorption effect on certain poisons, which can protect the main active sites from damage. The multi-level pore structure ensures that even if some pores are blocked, sufficient active channels can still be maintained. This structural stability ensures that the performance of the catalyst will decay slowly during long-term operation.

[0029] Preferably, as a further specific embodiment, the adsorbent is modified activated carbon or molecular sieve, wherein the modified activated carbon has a pore size distribution of 2-10 nm and a specific surface area of 800-1200 m 2 / g, and 0.5-2wt% of copper oxide is loaded on the surface; the molecular sieve is of ZSM-5 type, with a silicon-aluminum ratio of 20-50, and is impregnated with ammonium dihydrogen phosphate solution.

[0030] In addition, the present invention also specifically defines the adsorbent. By selecting modified activated carbon or molecular sieve as the adsorption material and precisely controlling its physical and chemical parameters, a highly efficient and coordinated terminal purification system is constructed. This technical feature fundamentally solves the key problems of incomplete removal of fine dust and escape of residual pollutants in traditional flue gas treatment processes. The pore size distribution of the modified activated carbon is strictly controlled within the range of 2-10nm. Although micropores below 2nm can provide a huge specific surface area, they are easily blocked due to capillary condensation, which is more obvious when treating high-humidity flue gas; and 10nm Although the above large pores are conducive to mass transfer, they will significantly reduce the adsorption capacity. Therefore, the mesopore distribution of 2-10nm just balances the contradiction between adsorption kinetics and thermodynamics. It can not only effectively capture fine particles below PM2.5, but also provide a fast channel for the diffusion of gas molecules. This "molecular sieve" effect ensures that the adsorbent maintains stable purification efficiency during long-term operation. In addition, too low specific surface area will lead to insufficient active sites, while too high a value may cause the material structure to be fragile and the cost to surge. This optimized range not only ensures sufficient adsorption sites, but also maintains the structural stability and economic feasibility of the material.

[0031] The 0.5-2wt% copper oxide loading on the activated carbon surface embodies the synergistic concept of adsorption and catalysis. The introduction of copper oxide nanoparticles constructs a multifunctional active interface. From the perspective of physical adsorption, the heterojunction interface formed by copper oxide and the activated carbon surface produces additional defect sites, enhancing the adsorption capacity of polar pollutants. From the perspective of chemical conversion, these highly dispersed copper oxide nanoparticles can catalyze the continued reaction of NOx and escaped NH3 at low temperatures, realizing the combination of adsorption enrichment and in situ conversion. This "adsorption-catalysis" coupling mechanism greatly improves purification efficiency, especially for low-concentration pollutants that are difficult to treat with traditional technologies. It shows excellent removal effects. The copper oxide loading is precisely controlled in the range of 0.5-2wt%, which not only avoids pore blockage caused by excessive loading, but also ensures sufficient active site density.

[0032] As an alternative, the ZSM-5 molecular sieve has also been carefully optimized, with the silicon-aluminum ratio controlled within the range of 20-50 to balance acidity and thermal stability. Although a lower silicon-aluminum ratio can provide more acid sites, it will lead to a decrease in hydrothermal stability; while a too high silicon-aluminum ratio will result in insufficient acidity and affect adsorption performance. The silicon-aluminum ratio range of 20-50 allows the molecular sieve to maintain sufficient acid sites while being able to withstand the effects of water vapor and temperature fluctuations in the flue gas. At the same time, the surface properties of the molecular sieve are further regulated by the impregnation treatment with ammonium dihydrogen phosphate solution. The introduction of phosphate groups enhances the surface acidity, while ammonium ions provide additional NH 4+ Active sites, this dual modification enables the molecular sieve to exhibit a broad spectrum of adsorption capabilities for a variety of pollutants.

[0033] Preferably, as a further specific embodiment, a transition buffer zone is provided between the catalytic reaction zone and the deep purification zone, and the transition buffer zone is filled with a honeycomb cordierite carrier, the surface of which is loaded with a MnOx-CuO two-component catalyst.

[0034] In addition, the present invention also provides a transition buffer zone between the corrugated plate catalyst and the adsorbent. The buffer zone is filled with a honeycomb cordierite carrier and loaded with a MnOx-CuO two-component catalyst, thereby effectively solving the key problem of poor connection between the reaction zone and the purification zone in traditional flue gas treatment processes, which leads to reduced efficiency. After the flue gas passes through the front-stage corrugated plate catalyst treatment, although most of the NOx has been reduced, some unreacted NO, escaped NH3, and intermediate products generated in the front stage may still remain. If these components enter the deep purification zone directly, they will not only increase the burden on the adsorbent but may also cause unnecessary side reactions. Among them, cordierite, as a commonly used carrier for industrial catalysts, has excellent thermal stability and mechanical strength. Its honeycomb structure creates uniform airflow distribution and low pressure drop. This regular channel arrangement forms a good fluid dynamic connection with the front and rear corrugated plate catalyst and adsorbent bed layers, avoiding vortices and short-circuiting caused by sudden flow field changes in traditional processes, and ensuring that the residence time distribution of the flue gas in the transition zone is more uniform and controllable.

[0035] At the same time, the loading of the MnOx-CuO two-component catalyst is the core of realizing the transition buffer function. The combination of these two transition metal oxides produces a remarkable synergistic catalytic effect. MnOx, with its rich redox properties and multiple valence states, becomes a highly efficient catalyst for the oxidation of NO to NO2. This conversion is crucial because NO2 has a higher reactivity than NO and is more easily captured or further reduced by subsequent adsorbents. The introduction of CuO compensates for the lack of low-temperature activity of MnOx. The interfacial active sites formed by CuO and MnOx can promote the activation of NH3 and effectively utilize the escaped NH3 for the removal of residual NOx. It is particularly noteworthy that the MnOx-CuO ratio has been carefully optimized and is usually controlled in the range of Mn:Cu molar ratio of 3:1 to 5:1. This ratio ensures sufficient oxidation capacity while maintaining good low-temperature activity.

[0036] Preferably, as a further specific embodiment, the alkaline solution is a mixed solution of sodium hydroxide and sodium carbonate, and the mass ratio of the two is 1:1-1:3.

[0037] Preferably, as a further specific embodiment, 0.1-0.5 wt% of a composite auxiliary agent is further added to the wet scrubbing method, and the composite auxiliary agent is composed of sodium polyacrylate and sodium dodecylbenzene sulfonate in a mass ratio of 1:1-1:3.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention provides a flue gas dust removal and denitrification process, which solves the problems of low dust removal and denitrification efficiency, easy catalyst deactivation, and high operating costs in traditional technologies through process integration and material innovation. It has the advantages of high purification efficiency, low energy consumption and a wide range of applications. DETAILED DESCRIPTION

[0040] The technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. However, those skilled in the art will understand that the embodiments described below are part of the embodiments of the present invention, not all of them, and are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] In order to more clearly illustrate the technical solutions of the present invention, specific embodiments are provided below for illustration.

[0042] Example 1

[0043] The specific implementation method of the flue gas dust removal and denitrification process of the present invention is as follows:

[0044] 1. Pretreatment area operation

[0045] The flue gas generated by the coal-fired boiler (temperature 280℃, dust concentration 150mg / m 3 , NOx concentration 450mg / m 3 , SO2 concentration 800mg / m 3 ) is passed into the pretreatment zone and wet scrubbing is performed using a three-stage spray tower; the spray liquid is an alkaline solution with a pH of 8 (sodium hydroxide and sodium carbonate mixed in a mass ratio of 1:1), the volume ratio of the spray liquid to the flue gas is 1:50, and 0.1wt% of a composite auxiliary agent (sodium polyacrylate and sodium dodecylbenzene sulfonate in a mass ratio of 1:1) is added to the spray liquid;

[0046] After treatment, the removal rate of large dust particles (>10μm) in the flue gas reaches 98%, the SO2 removal rate is 65%, and the outlet flue gas temperature drops to 200℃;

[0047] 2. Preparation of corrugated plate catalyst and operation of catalytic reaction zone

[0048] (1) Catalyst preparation:

[0049] Preparation of porous cordierite ceramic matrix by extrusion molding:

[0050] Raw material ratio: cordierite powder (particle size 5-10 μm) 85 wt%, pore-forming agent (methyl cellulose) 10 wt%, binder (polyvinyl alcohol) 5 wt% are mixed evenly;

[0051] Deionized water was added to prepare a plastic clay (water content 25%), and after vacuum kneading, the clay was extruded through a mold to obtain a wet embryo. The mold was designed to have a sinusoidal waveform (wave height 5 mm, wave distance 10 mm);

[0052] After the wet billet was aged for 24 hours in a humidity environment of 90%, it was dried by programmed temperature increase (50°C × 2 hours → 80°C × 2 hours → 110°C × 4 hours);

[0053] High-temperature sintering: heating to 600°C at 2°C / min and holding for 2 hours (to remove organic matter), then heating to 1350°C at 5°C / min and sintering for 6 hours. After natural cooling, a cordierite ceramic matrix with a porosity of 40% was obtained;

[0054] 2. Active ingredient loading

[0055] The VW-Ti active component is loaded by impregnation method:

[0056] Prepare a mixed solution: ammonium metavanadate (0.5 mol / L), ammonium metatungstate (0.5 mol / L), and tetrabutyl titanate (1.0 mol / L) at a molar ratio of V:W:Ti = 1:1:2;

[0057] The cordierite ceramic substrate was immersed in the mixed solution (liquid-to-solid ratio 10:1) and ultrasonically assisted impregnation was performed for 30 min;

[0058] After removing excess solution by centrifugation, the mixture was dried at 120 °C for 12 h;

[0059] Calcination process: heat to 300℃ at 2℃ / min and keep for 2h, then heat to 500℃ at 5℃ / min and calcine for 4h to obtain a specific surface area of 50m 2 / g of supported catalyst precursor.

[0060] 3. Carbon Nanotube Network Construction

[0061] Embedding of amino-modified carbon nanotubes by chemical vapor deposition (CVD):

[0062] The supported catalyst precursor was placed in a tube furnace and introduced with ethylenediamine (carbon source) and argon (carrier gas) at a flow ratio of 1:10;

[0063] The reaction was carried out at 650°C for 2 h, and the amount of carbon nanotubes grown was controlled to be 5% of the total weight of the catalyst;

[0064] Ammonia gas was introduced (300°C × 1h) to carry out surface amino modification to form functional groups to obtain a crude catalyst;

[0065] 4. Preparation of Nano-Silica Protective Layer

[0066] Sol-gel coating of the doped protective layer:

[0067] Preparation of silica sol: ethyl orthosilicate: ethanol: water = 1:10:5 (molar ratio), adjust pH to 3.5 with hydrochloric acid, and hydrolyze at 60°C for 4 h;

[0068] Adding cerium oxide precursor (cerium ammonium nitrate) and platinum nanoparticles (prepared by ethylene glycol reduction method, particle size 3-5nm) so that the final product contains 1% CeO2 and 0.05wt% Pt in 1% CeO2;

[0069] The crude catalyst was immersed in the sol (immersion time 30s) and the pulling speed was 5cm / min to form a wet film;

[0070] After drying at 100 °C, heat treatment was performed at 450 °C for 2 h to obtain a dense protective layer with a thickness of 0.1 μm;

[0071] (2) Catalytic reaction:

[0072] The pretreated flue gas was introduced into the catalytic reaction zone, and 10% ammonia water (NH3 / NOx molar ratio 0.9) was sprayed into the corrugated plate catalyst bed (space velocity 3000h-1). The reaction temperature was controlled at 220°C. The measured NOx conversion rate reached 92%, and the ammonia slip was <5ppm.

[0073] 3. Setting of transition buffer

[0074] A transition buffer zone was set between the catalytic reaction zone and the deep purification zone, filled with a honeycomb cordierite support (pore density 300 cpsi), and loaded with a MnOx-CuO two-component catalyst (Mn:Cu molar ratio 4:1, loading amount 15 wt%) by impregnation method;

[0075] The buffer zone temperature is controlled at 200°C to convert residual NO into NO2 and further reduce the ammonia escape concentration to below 3ppm.

[0076] 4. Preparation and operation of adsorbent in deep purification area

[0077] Preparation of modified activated carbon:

[0078] Select coconut shell activated carbon (specific surface area 800m 2 / g), and the pore size was adjusted to the range of 2-10 nm by steam activation;

[0079] The modified activated carbon was loaded with 0.5 wt% copper oxide (copper nitrate as precursor) by the equal volume impregnation method and calcined at 300 °C.

[0080] Purification operation: The flue gas passes through the deep purification zone at a flow rate of 1m / s, using modified activated carbon, controlling the operating temperature at 150℃, and finally discharges the flue gas.

[0081] Example 2

[0082] The specific implementation method of the flue gas dust removal and denitrification process of the present invention is as follows:

[0083] 1. Pretreatment area operation

[0084] The flue gas generated by the coal-fired boiler (temperature 280℃, dust concentration 150mg / m 3 , NOx concentration 450mg / m 3 , SO2 concentration 800mg / m 3 ) is passed into the pretreatment area and wet scrubbed using a three-stage spray tower. The spray liquid is an alkaline solution with a pH of 10 (sodium hydroxide and sodium carbonate mixed in a mass ratio of 1:3), and the volume ratio of spray liquid to flue gas is 1:100. 0.5 wt% of a composite additive (sodium polyacrylate and sodium dodecylbenzene sulfonate in a mass ratio of 1:3) is added to the spray liquid.

[0085] After treatment, the removal rate of large dust particles (>10μm) in the flue gas reaches 98%, the SO2 removal rate is 65%, and the outlet flue gas temperature drops to 200℃;

[0086] 2. Preparation of corrugated plate catalyst and operation of catalytic reaction zone

[0087] (1) Catalyst preparation:

[0088] Preparation of porous cordierite ceramic matrix by extrusion molding:

[0089] Raw material ratio: cordierite powder (particle size 5-10 μm) 85 wt%, pore-forming agent (methyl cellulose) 10 wt%, binder (polyvinyl alcohol) 5 wt% are mixed evenly;

[0090] Deionized water was added to prepare a plastic clay (water content 25%), and after vacuum kneading, the clay was extruded through a mold to obtain a wet embryo. The mold was designed to have a sinusoidal waveform (wave height 20 mm, wave distance 50 mm);

[0091] After the wet billet was aged for 24 hours in a humidity environment of 90%, it was dried by programmed temperature increase (50°C × 2 hours → 80°C × 2 hours → 110°C × 4 hours);

[0092] High-temperature sintering: heating to 600°C at 2°C / min and holding for 2 hours (to remove organic matter), then heating to 1350°C at 5°C / min and sintering for 6 hours. After natural cooling, a cordierite ceramic matrix with a porosity of 70% was obtained;

[0093] 2. Active ingredient loading

[0094] The VW-Ti active component is loaded by impregnation method:

[0095] Prepare a mixed solution: ammonium metavanadate (0.5 mol / L), ammonium metatungstate (0.5 mol / L), and tetrabutyl titanate (1.0 mol / L) at a molar ratio of V:W:Ti = 1:1:2;

[0096] The cordierite substrate was immersed in the mixed solution (liquid-to-solid ratio 10:1) and ultrasonically assisted impregnation was performed for 30 min;

[0097] After removing excess solution by centrifugation, the mixture was dried at 120 °C for 12 h;

[0098] Calcination process: heat to 300℃ at 2℃ / min and keep for 2h, then heat to 500℃ at 5℃ / min and calcine for 4h to obtain a specific surface area of 200m 2 / g of supported catalyst precursor.

[0099] 3. Carbon Nanotube Network Construction

[0100] Embedding of amino-modified carbon nanotubes by chemical vapor deposition (CVD):

[0101] The supported catalyst precursor was placed in a tube furnace and introduced with ethylenediamine (carbon source) and argon (carrier gas) at a flow ratio of 1:10;

[0102] The reaction was carried out at 650°C for 2 h, and the amount of carbon nanotubes grown was controlled to be 5% of the total weight of the catalyst;

[0103] Ammonia gas was introduced (300°C × 1h) to carry out surface amino modification to form functional groups to obtain a crude catalyst;

[0104] 4. Preparation of Nano-Silica Protective Layer

[0105] Sol-gel coating of the doped protective layer:

[0106] Preparation of silica sol: ethyl orthosilicate: ethanol: water = 1:10:5 (molar ratio), adjust pH to 3.5 with hydrochloric acid, and hydrolyze at 60°C for 4 h;

[0107] Adding cerium oxide precursor (cerium ammonium nitrate) and platinum nanoparticles (prepared by ethylene glycol reduction method, particle size 3-5nm) so that the final product contains 3% CeO2 and 0.1wt% Pt in 3% CeO2;

[0108] The crude catalyst was immersed in the sol (immersion time 30s) and the pulling speed was 5cm / min to form a wet film;

[0109] After drying at 100 °C, heat treatment was performed at 450 °C for 2 h to obtain a dense protective layer with a thickness of 0.5 μm;

[0110] (2) Catalytic reaction:

[0111] The pretreated flue gas was introduced into the catalytic reaction zone, and 10% ammonia water (NH3 / NOx molar ratio 0.9) was sprayed into the corrugated plate catalyst bed (space velocity 3000h-1). The reaction temperature was controlled at 220°C. The measured NOx conversion rate reached 92%, and the ammonia slip was <5ppm.

[0112] 3. Setting of transition buffer

[0113] A transition buffer zone was set between the catalytic reaction zone and the deep purification zone, filled with a honeycomb cordierite support (pore density 300 cpsi), and loaded with a MnOx-CuO two-component catalyst (Mn:Cu molar ratio 4:1, loading amount 15 wt%) by impregnation method;

[0114] The buffer zone temperature is controlled at 200°C to convert residual NO into NO2 and further reduce the ammonia escape concentration to below 3ppm.

[0115] 4. Preparation and operation of adsorbent in deep purification area

[0116] Molecular sieve preparation:

[0117] ZSM-5 molecular sieve (silicon-aluminum ratio 20) was selected and immersed in 0.5 mol / L ammonium dihydrogen phosphate solution for 2 hours, dried at 120°C and then calcined at 500°C to obtain the molecular sieve;

[0118] Purification operation: The flue gas passes through the deep purification zone at a flow rate of 1m / s, using molecular sieves and controlling the operating temperature at 150°C. The flue gas is finally discharged.

[0119] Example 3

[0120] The specific implementation method of the flue gas dust removal and denitrification process of the present invention is as follows:

[0121] 1. Pretreatment area operation

[0122] The flue gas generated by the coal-fired boiler (temperature 280℃, dust concentration 150mg / m 3 , NOx concentration 450mg / m 3 , SO2 concentration 800mg / m 3 ) is passed into the pretreatment area and wet scrubbed using a three-stage spray tower. The spray liquid is an alkaline solution with a pH of 9.5 (a mixture of sodium hydroxide and sodium carbonate in a mass ratio of 1:2), with a spray liquid to flue gas volume ratio of 1:60. 0.3 wt% of a composite additive (sodium polyacrylate and sodium dodecylbenzene sulfonate in a mass ratio of 1:2) is added to the spray liquid.

[0123] After treatment, the removal rate of large dust particles (>10μm) in the flue gas reaches 98%, the SO2 removal rate is 65%, and the outlet flue gas temperature drops to 200℃;

[0124] 2. Preparation of corrugated plate catalyst and operation of catalytic reaction zone

[0125] (1) Catalyst preparation:

[0126] Preparation of porous cordierite ceramic matrix by extrusion molding:

[0127] Raw material ratio: cordierite powder (particle size 5-10 μm) 85 wt%, pore-forming agent (methyl cellulose) 10 wt%, binder (polyvinyl alcohol) 5 wt% are mixed evenly;

[0128] Deionized water was added to prepare a plastic clay (water content 25%), and after vacuum kneading, the clay was extruded through a mold to obtain a wet embryo. The mold was designed to have a sinusoidal waveform (wave height 10 mm, wave distance 30 mm);

[0129] After the wet billet was aged for 24 hours in a humidity environment of 90%, it was dried by programmed temperature increase (50°C × 2 hours → 80°C × 2 hours → 110°C × 4 hours);

[0130] High-temperature sintering: heating to 600°C at 2°C / min and holding for 2 hours (to remove organic matter), then heating to 1350°C at 5°C / min and sintering for 6 hours. After natural cooling, a cordierite ceramic matrix with a porosity of 40% was obtained;

[0131] 2. Active ingredient loading

[0132] The VW-Ti active component is loaded by impregnation method:

[0133] Prepare a mixed solution: ammonium metavanadate (0.5 mol / L), ammonium metatungstate (0.5 mol / L), and tetrabutyl titanate (1.0 mol / L) at a molar ratio of V:W:Ti = 1:1:2;

[0134] The cordierite substrate was immersed in the mixed solution (liquid-to-solid ratio 10:1) and ultrasonically assisted impregnation was performed for 30 min;

[0135] After removing excess solution by centrifugation, the mixture was dried at 120 °C for 12 h;

[0136] Program calcination: heat to 300℃ at 2℃ / min and keep for 2h, then heat to 500℃ at 5℃ / min and calcine for 4h to obtain a specific surface area of 100m 2 / g of supported catalyst precursor.

[0137] 3. Carbon Nanotube Network Construction

[0138] Embedding of amino-modified carbon nanotubes by chemical vapor deposition (CVD):

[0139] The supported catalyst precursor was placed in a tube furnace and introduced with ethylenediamine (carbon source) and argon (carrier gas) at a flow ratio of 1:10;

[0140] The reaction was carried out at 650°C for 2 h, and the amount of carbon nanotubes grown was controlled to be 5% of the total weight of the catalyst;

[0141] Ammonia gas was introduced (300°C × 1h) to carry out surface amino modification to form functional groups to obtain a crude catalyst;

[0142] 4. Preparation of Nano-Silica Protective Layer

[0143] Sol-gel coating of the doped protective layer:

[0144] Preparation of silica sol: ethyl orthosilicate: ethanol: water = 1:10:5 (molar ratio), adjust pH to 3.5 with hydrochloric acid, and hydrolyze at 60°C for 4 h;

[0145] Adding cerium oxide precursor (cerium ammonium nitrate) and platinum nanoparticles (prepared by ethylene glycol reduction method, particle size 3-5 nm) so that the final product contains 2% CeO2 and 0.08wt% Pt in 2% CeO2;

[0146] The crude catalyst was immersed in the sol (immersion time 30s) and the pulling speed was 5cm / min to form a wet film;

[0147] After drying at 100 °C, heat treatment was performed at 450 °C for 2 h to obtain a dense protective layer with a thickness of 0.3 μm;

[0148] (2) Catalytic reaction:

[0149] The pretreated flue gas was introduced into the catalytic reaction zone, and 10% ammonia water (NH3 / NOx molar ratio 0.9) was sprayed into the corrugated plate catalyst bed (space velocity 3000h-1). The reaction temperature was controlled at 220°C. The measured NOx conversion rate reached 92%, and the ammonia slip was <5ppm.

[0150] 3. Setting of transition buffer

[0151] A transition buffer zone was set between the catalytic reaction zone and the deep purification zone, filled with a honeycomb cordierite support (pore density 300 cpsi), and loaded with a MnOx-CuO two-component catalyst (Mn:Cu molar ratio 4:1, loading amount 15 wt%) by impregnation method;

[0152] The buffer zone temperature is controlled at 200°C to convert residual NO into NO2 and further reduce the ammonia escape concentration to below 3ppm.

[0153] 4. Preparation and operation of adsorbent in deep purification area

[0154] Molecular sieve preparation:

[0155] ZSM-5 molecular sieve (silicon-aluminum ratio 30) was selected and immersed in 0.5 mol / L ammonium dihydrogen phosphate solution for 2 hours, dried at 120°C and then calcined at 500°C to obtain the molecular sieve;

[0156] Purification operation: The flue gas passes through the deep purification zone at a flow rate of 1m / s, using molecular sieves and controlling the operating temperature at 150°C. The flue gas is finally discharged.

[0157] Comparative Example 1

[0158] The specific implementation method is consistent with Example 3, except that a transition buffer zone is not provided between the catalytic reaction zone and the deep purification zone.

[0159] Experimental Example 1 Flue gas dust removal and denitrification performance test

[0160] 1. Test Method

[0161] The flue gas treatment systems in Examples 1-3 were tested for 72 hours of continuous operation to measure the following indicators:

[0162] Dust removal efficiency: Laser particle size analyzer detects dust concentration at the inlet and outlet;

[0163] Denitrification efficiency: Chemiluminescence NOx analyzer detects NOx concentration;

[0164] SO2 removal rate: UV fluorescence SO2 analyzer;

[0165] Ammonia escape: indigo blue spectrophotometry;

[0166] System pressure drop: differential pressure transmitter monitoring;

[0167] Catalyst stability: Sampling is conducted every 8 hours to test the activity decay rate;

[0168] The test results of the final examples 1-3 are shown in Table 1 below;

[0169] Table 1 Test results

[0170]

[0171]

[0172] The test results of Examples 1-3 of the present invention fully demonstrate the excellent performance and technological innovation of the flue gas dust removal and denitrification process. As can be seen from the data in Table 1, the three examples are significantly superior to the traditional process in key indicators such as PM2.5 removal rate, NOx removal rate, SO2 synergistic removal rate, ammonia slip control, and catalyst stability. Therefore, it can be seen that the present invention has constructed an efficient, stable, and economical multi-pollutant synergistic control system through the system integration of pretreatment optimization, catalyst innovation, transition zone connection, and deep purification. Its technical indicators not only comprehensively surpass traditional processes, but also show significant environmental and economic benefits in actual industrial applications, providing a landmark solution in the field of flue gas purification.

[0173] The data from Comparative Example 1 shows that when a transition buffer zone is not provided between the catalytic reaction zone and the deep purification zone, the denitrification effect is generally degraded. This indicates that the transition buffer zone significantly improves overall denitrification efficiency and reduces byproduct emissions through the oxidation of residual NO by the MnOx-CuO catalyst and the secondary utilization of escaped NH3. Furthermore, the absence of a transition buffer zone results in a poor connection between the catalytic reaction zone and the deep purification zone, preventing the effective conversion of unreacted NOx and NH3 in the flue gas. This directly increases the adsorbent burden and, in turn, affects the ultimate PM2.5 removal effect.

[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flue gas dust removal and denitrification process, characterized in that: The following steps are involved: The flue gas to be treated is passed into the pretreatment area, and a wet scrubbing method is used to remove large dust particles and some acidic gases in the flue gas. The wet scrubbing method adopts a multi-stage spraying system. The spraying liquid is an alkaline solution with a pH value of 8-10, and the volume ratio of the spraying liquid to the flue gas is 1:50-1:100; The treated flue gas is introduced into the catalytic reaction zone, and the reducing agent is sprayed into the flue gas under the action of the corrugated plate catalyst; The flue gas after the catalytic reaction is then passed into the deep purification zone, where adsorbent is used to adsorb and purify the remaining fine dust; The treated flue gas that meets the standards will then be discharged.

2. The flue gas dust removal and denitrification process according to claim 1, characterized in that: The corrugated plate catalyst is a supported metal oxide catalyst, and the active ingredients are a mixture of vanadium, tungsten and titanium; the corrugated plate structure of the corrugated plate catalyst is arranged in a sinusoidal or trapezoidal wave pattern, with a wave height of 5-20 mm and a wave distance of 10-50 mm; the carrier of the corrugated plate catalyst is porous cordierite ceramic.

3. The flue gas dust removal and denitrification process according to claim 2, characterized in that: The surface of the corrugated plate catalyst is coated with a nano-silicon dioxide protective layer, and the thickness of the nano-silicon dioxide protective layer is 0.1-0.5 μm.

4. The flue gas dust removal and denitrification process according to claim 3, characterized in that: The nano-silicon dioxide protective layer is doped with 1-3% of cerium oxide; the cerium oxide wraps platinum nanoparticles in a core-shell structure, and the content of the platinum nanoparticles is 0.05-0.1wt% of the mass of the cerium oxide.

5. The flue gas dust removal and denitrification process according to claim 2, characterized in that: The specific surface area of the corrugated plate catalyst is 50-200m 2 / g, and a porosity of 40-70%; a carbon nanotube network is embedded in the corrugated plate catalyst, and the surface of the carbon nanotube is modified with amino functional groups.

6. The flue gas dust removal and denitrification process according to claim 1, characterized in that: The adsorbent is modified activated carbon or molecular sieve, wherein the pore size distribution of the modified activated carbon is 2-10 nm and the specific surface area is 800-1200 m 2 / g, and 0.5-2wt% of copper oxide is loaded on the surface; the molecular sieve is of ZSM-5 type, with a silicon-aluminum ratio of 20-50, and is impregnated with ammonium dihydrogen phosphate solution.

7. The flue gas dust removal and denitrification process according to claim 1, characterized in that: A transition buffer zone is provided between the catalytic reaction zone and the deep purification zone. The transition buffer zone is filled with a honeycomb cordierite carrier, the surface of which is loaded with a MnOx-CuO two-component catalyst.

8. The flue gas dust removal and denitrification process according to claim 1, characterized in that: The alkaline solution is a mixed solution of sodium hydroxide and sodium carbonate, and the mass ratio of the two is 1:1-1:

3.

9. The flue gas dust removal and denitrification process according to claim 1, characterized in that: The wet scrubbing method further adds 0.1-0.5 wt% of a composite auxiliary agent, which is composed of sodium polyacrylate and sodium dodecylbenzene sulfonate in a mass ratio of 1:1-1:3.

Citation Information

Cited By

  • Yellow phosphorus tail gas purification device

    CN121945289A